Atom probe tomography for biomaterials and biomineralization. (August 2022) - Grandfield, Kathryn; Micheletti, Chiara; Deering, Joseph; Arcuri, Gabriel; Tang, Tengteng; Langelier, Brian
Abstract: Biominerals and biomaterials are part of our daily lives, from our skeleton and teeth to coral reefs and carbon-capturing single-cell organisms in the oceans, to engineered ceramics comprising our toothpaste and bone replacements. Many biominerals are hierarchically structured with remarkable material properties that arise from their unique combination of organic and inorganic components. Such structural hierarchy is often formed through a process of biomineralization. However, many fundamental questions remain regarding mineralization events in bones or teeth, and near biomaterials, partly due to the challenges in characterizing three-dimensional (3D) structure and chemical composition simultaneously at the nanometer scale. Atom probe tomography (APT) is a 3D characterization technique that combines both sub-nanometer spatial resolution and compositional sensitivity down to tens of parts per million. While APT is well-established in application to conventional engineering materials, recent years have seen its expansion into biomineralization research. Here, we focus our review on APT applications to biominerals, biomaterials and biointerfaces, providing a high-level summary of findings, as well as a primer on theory and best practices specific to the biomineralization community. We show that APT is a promising characterization tool, where its unique ability to quantify 3D chemical composition is not only complementary to other microscopy techniques but could become an integral part of biomaterial research. With the emerging trends of correlative and cryogenic workflow, notwithstanding the challenges outlined herein, APT has the potential to improve understanding of a broader range of biomaterials, while deriving innovative perspectives on clinical applications and strategies for biomaterial design. Statement of significance: Atom probe tomography (APT) is a three-dimensional characterization technique that can provide quantitative elemental and isotopic analysis with sub-nanometer resolution and compositional sensitivity down to tens of parts per million. These capabilities make it uniquely positioned for the analysis of biomineralized materials, both natural and synthetic. Here, we review the various applications of APT to the field of biomineralization, including applications in biominerals, biomaterials, biointerfaces and other biological materials, such as cells or proteins. A brief but comprehensive summary of the relevant technical concepts, limitations, and future perspectives to enable growth in this field are also included. Although APT is relatively new to the field of biomineralization, it has shown the potential to transform our basic understanding of biomineralization mechanisms and better inform biomaterials design. Graphical abstract: Image, graphical abstract